L-Shell Photoionization of Magnesium-like Ions with New Results for Cl5+ - Jean-Paul Mosnier; Eugene T. Kennedy; Jean-Marc Bizau; Denis Cubaynes; Ségolène Guilbaud; Christophe Blancard; M. Fatih Hasoğlu; Thomas W. Gorczyca (Atoms, 2023)
This study reports on the absolute photoionization cross sections for the magnesium-like Cl5+ ion over the 190–370 eV photon energy range, corresponding to the L-shell (2s and 2p subshells) excitation regime. The experiments were performed using the Multi-Analysis Ion Apparatus (MAIA) on the PLéIADES beamline at the SOLEIL synchrotron radiation storage ring facility. Single and double ionization ion yields, produced by photoionization of the 2p subshell of the Cl5+ ion from the 2p63s2 1S0 ground state and the 2p63s3p 3P0,1,2 metastable levels, were observed, as well as 2s excitations. Theoretical calculations of the photoionization cross sections using the Multi-Configuration Dirac-Fock and R-matrix approaches were carried out, and the results were compared with the experimental data. The Cl5+ results were examined within the overall evolution of L-shell excitation for the early members of the Mg-like isoelectronic sequence (Mg, Al+, Si2+, S4+, Cl5+). Characteristic photon energies for P3+ were estimated by interpolation.